Pengaruh Pendekatan Realistic Mathematic Education (RME) Terhadap Keterampilan Menyelesaikan Soal Cerita Ditinjau Dari Kemampuan Memahami Konsep Matematika - Salsabila, Siti Rima (Jurnal of Math Tadris, 2022)
Abstract-The Realistic Mathematical Education (RME) approach is based on the philosophy that mathematics must be associated with real things for students and mathematics must be seen as a human activity. This philosophy is in line with story problems that present problems from everyday life. This study aims to see whether or not there is an effect of the Realistic Mathematical Education (RME) Approach on the skills of solving word problems in terms of the ability to understand mathematical concepts. This research is quantitative experimental research. The population in this study were students of class VII MTs. Ishlahil Atfal Rumak. The research sample was the VII A class used as the control class and the VII C class used as the experimental class. The research instrument was a test of the ability to understand concepts and skills in solving word problems in essay form. The data on skills in solving word problems were analyzed using a two-way ANOVA test after fulfilling the normality and homogeneity tests. The results of data analysis showed Fcount <Ftable, namely -23.07 <3.28. Thus it can be concluded that there is no effect of the Realistic Mathematics Education (RME) approach on the skills of solving word problems in terms of the ability to understand mathematical concepts.